“He that is without sin among you, let him first cast a stone at her…” (Theological Kronos, 2024)
This article presents the results of an investigation on Gender-Based Violence (GBV) in the context of evangelical churches in Cali.  It defines the most common forms of violence in the ecclesiastical or religious field and shares the justification for these forms of violence, many of which are mediated by a patriarchal interpretation of the Holy Scriptures. Next, some relevant themes are presented, such as religious hegemony, abuse of power, patriarchal interpretation of biblical texts, the masculine perspective of the Divinity and rigid structures, as support for these GBV in the ecclesial and ministerial spaces that emerged as a result of the research. The article ends with a call to the churches to pay attention to this violence and to take corrective measures of visibility and action.
Keywords: Forms of violence; power; church; women; bible and research